Managing Anxiety in The Middle of The Covid-19 Pandemic - Choeron, Rachmat Chusnul; Ka’arayeno, Arie Jefry (Journal of Community Service for Health, 2022)
The Covid-19 pandemic is a threat to all people in the world. High mortality and morbidity rates cause anxiety for most people. The purpose of this community service is to provide public knowledge in managing anxiety amid the COVID-19 pandemic. The method used in this community service is the lecture and discussion method. The target for this community service is 60 nursing professional students. The presentation of the material is carried out online through google meet. Anxiety is measured to find out how much anxiety is felt by students. Results. The results of measuring anxiety in nursing profession students found that most of the students had anxiety in the moderate category (55.00%). These results indicate that the COVID-19 pandemic has a real impact on student anxiety. This is due to the fear of being exposed to Covid-19 at any time. It is very important to carry out health education to the community to help the community overcome health problems or minimize the risk of health problems, including anxiety problems due to the threat of the COVID-19 pandemic.